The relationship between the attributes of procurement officers and the attributes of successful project management with the influence of procurement procedure in information system outsourcing: A systematic literature review - Ahmad, Azran; Arshad, Noor Habibah; Syed Aris, Sharipah Ruzaini (2016)
The utilization of ICT in organizations is increasing from time to time.The Malaysian Public Sector agencies have responded positively in utilizing ICT to enhance the efficiency and effectiveness of the services offered. To cope with the demand, the development of ICT projects needs to be implemented through outsourcing. The outsourcing method has brought together issues and problems that affect project success which need to be undertaken.Based on previous research, there are lots of deliberations on the factors that influence the project success of outsourced project implementation.In spite of that, the discussion on project management success (PMS) factors that concentrate on the competency measurement for department’s officers who are managing the procurement process has not sufficiently been clarified.The aim of this systematic literature review (SLR) is to identify the common attributes that influence project management success through the procurement procedure carried out by the procurement officer (PO). The outcome of the review explained the important relationship pattern between the identified attributes which will be applied in the future empirical and exploratory survey that will be carried out.Addition to this, the competency measurement model of ICT procurement officer will be developed.